Relationship Between Fatty Acid Binding Protein 4 and Liver Fat in Individuals at Increased Cardiometabolic Risk - Rodríguez-Calvo, Ricardo; Moreno-Vedia, Juan; Girona, Josefa; Ibarretxe, Daiana; Martínez-Micaelo, Neus; Merino, Jordi; Plana, Nuria; Masana, Lluis (Frontiers in Physiology, 2021)
Background: Liver steatosis is considered the onset of the non-alcoholic fatty liver disease (NAFLD), a major public health challenge. Nevertheless, NAFLD detection and diagnosis remain a difficult task. Fatty acid binding protein 4 (FABP4) has been proposed as potential biomarker for the ectopic fat accumulation in non-adipose tissues, although its role reflecting liver steatosis in metabolic patients is not fully explored. The aim of this study was to assess the relationship between FABP4 and the Fatty Liver Index (FLI) in metabolic patients and to evaluate its potential role in the fatty liver disease. Methods: A cross-sectional study involving 389 participants at increased cardiometabolic risk was performed. FLI was calculated in order to assess liver fatty disease and a FLI >60 was considered to define liver steatosis. The serum FABP4 levels were assessed by using a sandwich enzyme-linked immunosorbent assay. Multivariable regression models were used to examine the associations of FABP4 with fatty liver after adjusting for demographic and clinical characteristics. Results: Both, FLI and serum FABP4 levels were upregulated in diabetic, obese and metabolic syndrome patients. Serum FABP4 levels were higher in individuals with liver steatosis. Serum FABP4 were robustly associated with FLI in metabolic patients in both linear and logistic regression analyses. Conclusion: Our findings show that the serum FABP4 is associated to liver steatosis in metabolic patients.